Pain-induced skin autoimmunity - Odoardi, Francesca; Neuhuber, Winfried; Fluegel, Alexander (Cell Research, 2014)
A recent paper published in Nature reports sensory nerve fibers in the skin that give local immune cells important instructions for the organization of an immune response; in this particular case the cooperation between the nervous and immune systems had disastrous consequences, namely an auto-destruction of the skin.
EVALuna2:4145